Análisis de un control para la gestión de inventario en el Bazar Alvarado periodo 2019 - Filian Burgos, Pedro Junior (2020)
In this present summary we talk about what is inventory management where proper planning is offered, which must be oriented with a control and evaluation direction, making known the activities carried out by the commercial premises as such, or to maintain a level quality of the operations carried out within it. Since this allows through a control to obtain relevant information about a process with the purpose that complements the objective, correcting in time and on the fly that it performs in faults that can be observed. To maintain control, a specific inventory management must be done in any organization or company that is based on maintaining a clear and precise control that helps to give results of the information that is managed to achieve decision-making towards the objective that is aimed, for your business to emerge and benefit in order to know the importance of the tool that will help you to have timely information. Heading in this case analysis, he faces through research tools such as interview and questionnaire, where anomalies reflected in inventory management were noted by which he investigated the business owner towards the commercial trajectory, where to find out some solutions that I proposed as a Management Control study, it was given some guidelines and inventory techniques and a control system that will be managed within the commercial premises.